PERANCANGAN FASILITAS PENDIDIKAN BERTINGKAT UNTUK ANAK USIA DINI MENGGUNAKAN METODE INOVASI FUNGSI DENGAN PENEKANAN ISU KESELAMATAN DAN PENCITRAAN ISLAM - Paryoko, Vijar Galax Putra Jagat (Universitas Atma Jaya Yogyakarta, 2020)
The development of early childhood education facilities at urban area, including islamic education, pressed to be realized as mulistorey buildings. Architecture design which has low awareness of particular characteristic of children activities would result on various weakness, such as children’s safety dan security. In addition, the lack of scientific publication regarding imaging of Islamic educational facility for children also an issue. Therefore, a qualitative research-based design is conducted to obtain efficient design solution which can reduce the construction cost, considering that it is a social building. The divergence phase aims to obtain criteria and solution alternatives from previous design through interviewing users and literature searchings, to be modified and combined. Innovation by voundary shifting, fucntional innovation, and precedent study methods are used to create design concepts. The ease for children activities to be supervised is achieved through centered spatial and circulation order. Children’s safety and security on their activities in multistorey buildings are preserved through the use of latest karawangan technology: laser cutting fiber cement which its cutting pattern is easily arraged, at the same time become a design solution for imaging islamic educational facility.